SARS-CoV-2 Infection during Pregnancy in a Rural Midwest All-delivery Cohort and Associated Maternal and Neonatal Outcomes - Steffen, Haley A.; Swartz, Samantha R.; Jackson, J. Brooks; Kenne, Kimberly A.; Ten Eyck, Patrick P.; Merryman, Abbey S.; Castaneda, Claire N.; Marsden, Katharine; Maxwell, Timothy; Merrill, Anna E.; Krasowski, Matthew D.; Rysavy, Mary B. (American Journal of Perinatology, 2021)
Objective This study aimed to estimate the prevalence of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) among pregnant patients at the time of delivery in a rural Midwest tertiary care hospital and to examine demographics, clinical factors, and maternal and neonatal outcomes associated with SARS-CoV-2 infection during pregnancy.Study Design This prospective cohort study included all delivering patients between May 1 and September 22, 2020 at the University of Iowa Hospitals and Clinics. Plasma SARS-CoV-2 antibody testing was performed. SARS-CoV-2 viral reverse-transcription polymerase chain reaction (RT-PCR) results and maternal and neonatal outcomes were collected from the electronic medical record. Data were analyzed using univariate statistical methods with clustering for multiple births.Results In total, 1,000 patients delivered between May 1 and September 22, 2020. Fifty-eight (5.8%) were SARS-CoV-2 antibody positive. Twenty-three also tested viral positive during pregnancy. Three of 1,000 (0.3%) were viral positive on admission but antibody negative. The median age was 30 years (interquartile range [IQR]: 26–33 years) and body mass index was 31.75 kg/m2 (IQR 27.7–37.5 kg/m2). The cesarean delivery rate was 34.0%. The study population was primarily white (71.6%); however, 41.0% of SARS-CoV-2 infected patients identified as Black, 18.0% as Hispanic/Latino, 3.3% as Native Hawaiian/Pacific Islander, and only 27.9% as White (p < 0.0001). SARS-CoV-2 infection was more likely in patients without private insurance (p = 0.0243). Adverse maternal and/or neonatal outcomes were not more likely in patients with evidence of infection during pregnancy. Two SARS-CoV-2 infected patients were admitted to the intensive care unit. There were no maternal deaths during the study period.Conclusion In this largely rural Midwest population, 6.1% of delivering patients had evidence of past or current SARS-CoV-2 infection. Rates of SARS-CoV-2 during pregnancy were higher among racial and ethnic minorities and patients without private insurance. The SARS-CoV-2 infected patients and their neonates were not found to be at increased risk for adverse outcomes.Key Points
Keywords: COVID-19; pregnancy; racial disparities; SARS-CoV-2; seroprevalence